PRAGMATIC FEATURES OF SYNONYMIC UNITS IN ENGLISH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article is devoted to the pragmatic characteristics of synonymic units in the English language. It highlights not only the semantic relatedness of synonyms but also the stylistic, emotional, and socio-pragmatic differences that emerge in their contextual use.